Atendimento Educacional Especializado e Práticas Pedagógicas Inclusivas - Carlo Schmidt; Eliana da Costa Pereira de Menezes; Clenio Perlin Berni; Carla Luciane Blum Vestena; Carla Maria de Schipper; Bernadete de Fatima Bastos Valentim (Universidade Federal de Santa Maria (UFSM), 2021)
Editorial